2018
DOI: 10.1016/j.athoracsur.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound to Detect Residual Pneumothorax After Chest Drain Removal in Lung Resections

Abstract: In this subgroup of patients with air leak of 10 to 20 mL/min, performing an imaging study to verify the absence of PTx is desirable; however, when LUS confirms lung expansion or the presence of apical PTx, CR does not seem to be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 24 publications
(37 reference statements)
2
35
0
Order By: Relevance
“…47 The absence of lung sliding or B-line to diagnose pneumothorax by LUS has a sensitivity of 88% to 100%. 48,49 Our study further con rmed the 90% sensitivity of LUS to diagnose pneumothorax. Because the thorax was opened for VATS, the pneumothorax was deemed residual gas.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…47 The absence of lung sliding or B-line to diagnose pneumothorax by LUS has a sensitivity of 88% to 100%. 48,49 Our study further con rmed the 90% sensitivity of LUS to diagnose pneumothorax. Because the thorax was opened for VATS, the pneumothorax was deemed residual gas.…”
Section: Discussionsupporting
confidence: 69%
“…Patella et al 48,50 demonstrated that LUS could also effectively and accurately evaluate the small amount of pneumothorax remaining after thoracic drainage, which was faster and more accurate than CXR. Senniappan's study suggested that LUS may be an alternative to CXR for the follow-up of pneumothorax due to its superior sensitivity, portability and reduction in radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Because the thorax was opened for VATS, the pneumothorax was deemed residual gas. Patella et al [47,49] demonstrated that LUS could also effectively and accurately evaluate the small amount of pneumothorax remaining after thoracic drainage, which was faster and more accurate than CXR. Senniappan's study suggested that LUS may be an alternative to CXR for the follow-up of pneumothorax due to its superior sensitivity, portability and reduction in radiation exposure [50].…”
Section: Discussionmentioning
confidence: 99%
“…in 2% of cases of transhiatal esophagectomy, which has similar surgical steps as in cervical esophageal exclusion. 4 Furthermore, our experience has shown that recanalization from titanium stapling has a variable time course, and recanalization at 2 weeks might not have achieved its objective of exclusion before healing is established. We also found that a full recanalization requires a few endoscopic balloon dilatations.…”
mentioning
confidence: 97%